2008
DOI: 10.1007/s12072-008-9095-9
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment and on-treatment predictors of viral breakthrough in lamivudine therapy for chronic hepatitis B

Abstract: Purpose There are remarkable advances in the treatment of chronic hepatitis B (CHB) in the last few years. Unfortunately, prolonged antiviral treatment is associated with increasing risk of drug resistance/viral breakthrough (VBT), which may lead to flare-up and rapid decompensation. We have designed this study to predict the pretreatment and on-treatment factors responsible for development of VBT. Methods This study was conducted during the period of February 2000 to November 2007. We have included 423 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
3
5
2
Order By: Relevance
“…However, this pre-treatment status did not significantly affect the development of VBT in the third year of treatment. These results disagree with those of studies conducted by Yuen (2001), Hadziyannis et al (2007), and Alam et al (2008), who found no significant relationship between the pre-treatment HBeAg status and rates of VBT.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…However, this pre-treatment status did not significantly affect the development of VBT in the third year of treatment. These results disagree with those of studies conducted by Yuen (2001), Hadziyannis et al (2007), and Alam et al (2008), who found no significant relationship between the pre-treatment HBeAg status and rates of VBT.…”
Section: Discussioncontrasting
confidence: 97%
“…We included in our analysis only those patients with ALT levels twice the normal limit. Our findings agree with those of Alam et al (2008) who also found no significant relationship between pre-treatment ALT levels and development of VBT.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations